Development of 2-axis solar panel for soil moisture detector at 4 seasons countries - Mohd Fadzil, Mat Isa (2010)
Photovoltaic (PV), is a technology in which light is converted into electrical power. One of the applications of PV is in solar tracker. Commercially, single-axis and two axis tracking mechanisms are available. Usually, the single axis tracker follows the Sun’s East-West movement, while the two-axis tracker follows the Sun’s changing altitude angle. To control the two axis solar panel so that it will always face the sun, the circuit will be programmed with 4 Light Dependent Resistor (LDR) as an input and 2 motor as an output. Both motor will be moved East-West and rotate around until both pair of LDR get the same percent of sunlight. It will move along the day follow to the sun. When the solar panel face directly to the sun and has maximum concentrated sunlight to the solar panel, the maximum power output will produce. The two axis solar tracker is design as active tracker and to make sure it can be used as a power supply especially in 4 seasons countries because in 4 seasons countries the sun rise and set in different angle for every seasons. It moves according to the sun movement and controlled by microcontroller. Besides that, solar tracker used to make sure have enough demand electricity, if not more photovoltaic module is needed where it is really expensive